Evaluation of ultrasonography and plethysmography in detecting blood loss and volume replacement in a platelet apheresis model - Kıvanç KARAMAN; Furkan Çağrı OĞUZLAR; Sinan SİTEMBÖLÜKBAŞI; Erşan KAYA (Heliyon)
Background: Rapid, reproducible, and noninvasive diagnostic methods like Ultrasonography (US) and plethysmographic measurements such as the perfusion index (PI) and pleth variablity index (PVI) have great potential value for emergency trauma cases in which blood loss needs to be recognized quickly and accurately. Objectives: We planned this study to evaluate the utility of US, PI, and PVI in detecting early-stage hemorrhage and mimicking volume replacement using a platelet apheresis model. Methods: This prospective, observational study included 46 healthy platelet apheresis volunteers who met inclusion criteria. Both of US measurements of Vena Cava Inferior (VCImin, VCImax, and VCIcı) and plethysmographic measurements were performed in three time period (before apheresis, after whole blood was collected, and after blood components except platelets were returned to donors). Results: Among the total 308 platelet apheresis, 46 male volunteers met inclusion criteria and consented to participate in the study. Of these 46 male volunteers, nine declined to have US measurements. After a mean blood loss of 440 ml in the first phase of apheresis, IVCmax decreased significantly, while pulse increased (p = 0.021 and p < 0.001, respectively). After the third phase of apheresis, which simulated volume replacement, IVCmin and IVCmax increased significantly, while pulse decreased (p = 0.003, p < 0.001, and p < 0.001, respectively). Conclusion: Per this platelet apheresis model, IVCmax is a diagnostic marker for both early-stage blood loss of less than 500 ml and volume replacement.